Constellation Design for Widely Linear Transceivers. (25th July 2010) - Lipardi Lipardi, Maddalena Maddalena; Mattera Mattera, Davide Davide; Sterle Sterle, Fabio Fabio
Abstract : Constellation design has been previously addressed by assuming that there is a linear equalizer at the receiver side. However, the widely linear equalizer is well known to outperform the linear one with no significant complexity increase; we derive optimum and suboptimum techniques for constellation design in presence of such an equalizer. The proposed techniques adapt the circularity properties of the transmitted signals to the specific channel to be equalized; their performance analysis shows that also the simplest suboptimum procedure provides significant improvements over a fixed-constellation scheme.